2018
DOI: 10.1016/j.burns.2018.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Research into Memory (PRiMe): Cognitive impairment following a severe burn injury and critical care admission, part 1

Abstract: Severe burns injuries are associated with a significant, global, cognitive deficit. Patients also report worse QoL, depression and post-traumatic stress. Perceived QoL from cognitive impairment was more closely associated with depression than cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 83 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…Of notice, this study showed that cognitive problems after burns persist beyond 18 months in about 35% of the patients, a health domain that has been scarcely studied in burn patients. A prior study reported cognitive problems in burn patients 2 years post-burn [40] and another study indicated that 16.6% of patients with minor burns and 33.3% of patients with severe burns experienced cognitive problems 5-7 years post-burn [41]. A positive association between PTSD symptoms and cognitive problems may be expected, because adults with PTSD show deficits in cognitive processes such as attention and executive functions [42,43].…”
Section: Discussionmentioning
confidence: 96%
“…Of notice, this study showed that cognitive problems after burns persist beyond 18 months in about 35% of the patients, a health domain that has been scarcely studied in burn patients. A prior study reported cognitive problems in burn patients 2 years post-burn [40] and another study indicated that 16.6% of patients with minor burns and 33.3% of patients with severe burns experienced cognitive problems 5-7 years post-burn [41]. A positive association between PTSD symptoms and cognitive problems may be expected, because adults with PTSD show deficits in cognitive processes such as attention and executive functions [42,43].…”
Section: Discussionmentioning
confidence: 96%
“…Burns have been shown to induce cognitive impairment and abnormal behavior (4,(8)(9)(10)(11)(12). Given the fact that BBB dysfunction is the key factor in cognitive impairment (50)(51)(52)(53)(54)(55)(56)(57) and that MSCs can effectively improve the integrity of BBB, we investigated whether burns could induce BBB dysfunction and neuroinflammation as well as evaluated its potential mechanism and the best time point for intervention to improve these effects after burn.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive dysfunction caused by peripheral trauma has been frequently reported, especially postoperative cognitive dysfunction (1)(2)(3) and cognitive dysfunction after burns (4)(5)(6)(7)(8)(9)(10)(11)(12). These severe central nervous system (CNS) complications burden the patients' families and the society.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, patients with severe burn injury are more likely to be hospitalized in the intensive care unit (ICU), having a higher risk of long-term cognitive impairments with common symptoms of memory defects (Duggan et al, 2017). The memory defects became the most distressing problems in these patients discharged from ICU (Pandharipande et al, 2013;Duggan et al, 2017), which affected up to two-thirds of patients (Wolters et al, 2013) and last for at least 2 years (Watson et al, 2018).…”
Section: Clinical Presentations and Outcomes Of Post-burn Cognitive S...mentioning
confidence: 99%